miR-7 and miR-34a sequence cloning and expression in a1235 glioblastoma cell line - Kolić, Dora (Array, 2020)
miRNAs are small non-coding RNAs which have an important role in signalling circuits regulating different cell processes. miR-7 and miR-34a are known as tumour suppressors, and both of them can interfere with cell proliferation, differentiation, apoptosis and migration. We constructed plasmids containing pri-miRNA sequences for these two miRNAs and introduced them into the A1235 glioblastoma cell line. Clones containing increased expression of processed miR-7 and miR-34a were obtained. The proliferation and sensitivity to alkylation agent of transfected cells were similar to those of control cells. Our results indicate that an increase in miR-7 and miR34 expression alone in A1235 glioblastoma cells is not sufficient to change their proliferation or sensitivity to the influence of alkylating agents.